Immediate metabolic availability of dietary fat in combination with carbohydrate. - Griffiths, A; Humphreys, S; Clark, M; Fielding, B; Frayn, K (1994)
We tested the hypothesis that when fat is ingested in combination with carbohydrate, direct release of fatty acids into the plasma may occur. Eight normal subjects ingested two meals: high-fat (80 g fat, 80 g carbohydrate, and 18 g protein) and low-fat (< 1 g fat, otherwise closely matched). Over the subsequent 6 h, net fat oxidation was greater after the high-fat meal (20.7 vs 10.6 g, P < 0.01). Plasma nonesterified fatty acid (NEFA) concentrations were markedly suppressed after the low-fat meal, but relatively maintained after the high-fat meal (P < 0.01). The profile of plasma NEFAs changed after the high-fat meal, consistent with entry of meal-derived fatty acids into the NEFA pool. We suggest that after ingestion of combinations of carbohydrate and fat, the action of lipoprotein lipase on chylomicron-triacylglycerol leads to direct release of fatty acids into the plasma and increased fat oxidation.